Evaluation of gamma response ability of single-mode and multi-mode optical fibers with different dopants as dosimeter sensors. (June 2022) - Asgari, S.; Jafari, H.; Taheri Ghahrizjani, R.; Feghhi, S.A.H.; Bataee, M.
Abstract: Optical fiber is used as a tool for data transmission in radiation environments in many applications such as medical, plasma diagnostics, and space satellites. The optical transmission is affected by ionizing radiation, characterized by radiation-induced attenuation. This feature allows use as a dosimeter sensor. In this work, the gamma radiation responses of three types of single-mode and multi-mode fibers, with different dopants of erbium (Er), germanium (Ge), and phosphorus (P) were evaluated. Radiation-induced attenuation was measured by spectrophotometer in wavelength ranges of 400–700 nm. The Er-doped fiber had higher attenuation of 0.8 dB/m after 560 mGy total dose. There was a reasonable linear relationship between the amount of attenuation and absorbed dose in P-, Ge-, and Er-doped fibers. Highlights: Radiation-induced attenuation (RIA) on optical transmission is used as a dosimeter. Multi- and single-mode fibers with different dopants of Er, Ge and P are evaluated. RIA is measured by spectrophotometer in optical wavelength ranges. There is a linear relation between RIA and absorbed dose in P- and Ge-doped fibers.